Oral contraceptives and female rowers' skeletal health - Redinger, A. L.; Baker, B. S. (The Journal of Strength and Conditioning Research, 2023)
Previous studies suggest that women using oral contraceptives (OC) experience fewer skeletal benefits from exercise compared with non-OC users. These findings may be especially important for athletes competing in weight-supported sports with a high prevalence of low bone mineral density and fracture, such as rowing. The purpose of this study was to examine skeletal health and bone injuries in collegiate female rowers. Forty-nine National Collegiate Athletic Association Division I female rowers completed general health, menstrual history, and bone physical activity questionnaire (BPAQ) surveys. Dual-energy X-ray absorptiometry (DXA) and peripheral quantitative computed tomography (pQCT) scans were used to assess bone content, density, and geometry. Contraceptive (OC users n = 14, non-OC users n = 35) and self-reported stress fracture (SFx n = 11, None n = 38) groups were analyzed using analysis of covariance and independent t-tests. Additionally, effect sizes (d) were calculated and significance was set at p = 0.05. Oral contraceptive users had reduced lumbar spine areal bone mineral density after adjustment for Total BPAQ (d = 0.58; p = 0.041) compared with non-OC users, but all other total body and site-specific DXA measures of bone mineral content and density were similar between contraceptive and injury groups. When comparing bone geometry of the 4, 38, and 66% tibiae using pQCT, no significant differences were found after adjustment for either contraceptive or injury group (all p > 0.060). Our findings suggest that OC usage was not associated with reduced skeletal health in competitive female rowers as evidenced by all Z-scores being above -2.0 and similar bone indices of mineralized content, density, geometry, and estimated strength between the groups.